Multi-Criteria Decision Making (MCDM) for technical evaluation of tenderers: A review of methods employed - Mohamed, Nor Hafizah; Lamsali, Hendrik; Sathyamoorthy, Dinesh (Science & Technology Research Institute for Defence (STRIDE), 2015)
Multi-criteria decision making (MCDM) is an area that is often discussed in operations research (OR).It is able to handle problems involving multiple criteria, and produce meaningful and quality decision making, especially in selecting the best alternative.This paper is aimed at reviewing the applications of MCDM for technical evaluation of tenderers.It identifies the problems that often occur in technical evaluation of tenderers.The MCDM techniques that have been employed to address these problems are then discussed, along with their benefits and limitations.Based on the review conducted, it can be suggested that analytical hierarchy process (AHP) is the most practical MCDM method for technical evaluation of tenderers, as it provides a fair and open process of assessment by taking into consideration the evaluators involved to avoid the issue of bias, and can be carried out with simplicity and transparency.Nonetheless, studies on other MCDM methods should be further explored due to the limitations of AHP.